Changing Blue Fluorescent Protein to Green Fluorescent Protein Using Chemical RNA Editing as a Novel Strategy in Genetic Restoration. (23rd June 2015) - Vu, Luyen T.; Nguyen, Thanh T. K.; Alam, Shafiul; Sakamoto, Takashi; Fujimoto, Kenzo; Suzuki, Hitoshi; Tsukahara, Toshifumi
Abstract : Using the transition from cytosine of BFP (blue fluorescent protein) gene to uridine of GFP (green fluorescent protein) gene at position 199 as a model, we successfully controlled photochemical RNA editing to effect site‐directed deamination of cytidine (C) to uridine (U). Oligodeoxynucleotides (ODNs) containing 5′‐carboxyvinyl‐2′‐deoxyuridine ( CV U) were used for reversible photoligation, and single‐stranded 100‐nt BFP DNA and in vitro ‐transcribed full‐length BFP mRNA were the targets. Photo‐cross‐linking with the responsive ODNs was performed using UV (366 nm) irradiation, which was followed by heat treatment, and the cross‐linked nucleotide was cleaved through photosplitting (UV, 312 nm). The products were analyzed using restriction fragment length polymorphism (RFLP) and fluorescence measurements. Western blotting and fluorescence‐analysis results revealed that in vitro ‐translated proteins were synthesized from mRNAs after site‐directed RNA editing. We detected substantial amounts of the target‐base‐substituted fragment using RFLP and observed highly reproducible spectra of the transition‐GFP signal using fluorescence spectroscopy, which indicated protein stability. ODNc restored approximately 10% of the C‐to‐U transition. Thus, we successfully used non‐enzymatic site‐directed deamination for genetic restoration in vitro . In the near future, in vivo studies that include cultured cells and model animals will be conducted to treat genetic disorders. Abstract : By using the transition from cytosine of BFP gene to uridine of GFP gene at position 199 as a model, we successfully controlled photochemical RNA editing to effect site‐directed deamination of cytidine to uridine. Western‐blotting and fluorescence‐analysis results revealed that the transition‐GFP protein was synthesized from mRNAs after site‐directed RNA editing.